2022
DOI: 10.3390/ijerph191811173
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Social Emotions, Perceived Efficiency, Transparency of the Government, Concerns about COVID-19, and Confidence in Fighting the Pandemic under the Week-Long Lockdown in Shenzhen, China

Abstract: The outbreak and spread of the COVID-19 pandemic have had a far-reaching impact. The present study investigated the factors primarily affecting the execution of the control measures, including social emotions, concerns about the pandemic, perceived efficiency, transparency of the government in publishing the pandemic-related information, and confidence in fighting the pandemic. Specifically, we examined the differences in these factors across four areas (i.e., lockdown area, control area, prevention area, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…More referentially, Shenzhen, China, experienced a week-long lockdown at the end of March. A study on this lockdown found a negative correlation between residents’ anger and confidence in anti-epidemic efforts [ 40 ]. The closed-loop management in the current study was extended over time, and no one knew how long it would last.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More referentially, Shenzhen, China, experienced a week-long lockdown at the end of March. A study on this lockdown found a negative correlation between residents’ anger and confidence in anti-epidemic efforts [ 40 ]. The closed-loop management in the current study was extended over time, and no one knew how long it would last.…”
Section: Discussionmentioning
confidence: 99%
“…The closed-loop management in the current study was extended over time, and no one knew how long it would last. Such uncertainty may exacerbate anger by influencing psychosocial factors such as confidence and trust [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the virus strains are capable of resisting natural or vaccine-elicited immunity and the absence of an effective treatment for COVID-19, the pandemic has significantly influenced and impacted human health and the economy ( Planas et al, 2022 ). Prolonged lockdowns and stringent screening policies have resulted in a heavy burden on governments, industries, organizations, and individuals ( Peng et al, 2022 , Dzimbiri et al, 2022 , Nazzal et al, 2022 ). Meanwhile, COVID-19 has also disturbed the healthcare systems in many countries worldwide ( Aymerich et al, 2022 , Andhavarapu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%